Expert clinicians' prototypes of an ideal child treatment in psychodynamic and cognitive-behavioral therapy: Is mentalization seen as a common process factor?. (2nd September 2016) - Goodman, Geoff; Midgley, Nick; Schneider, Celeste
Abstract: Objective: To investigate (a) whether expert clinicians within psychodynamic therapy (PDT) and cognitive-behavioral therapy (CBT) agree on key features of child psychotherapy process using the Child Psychotherapy Process Q-Set (CPQ); (b) whether these two prototypes can be empirically distinguished; and (c) whether promoting mentalization (operationalized as reflective functioning [RF]) is a shared component of the way expert clinicians conceptualize these two treatment models.Method: Thirty-one raters with expertise in PDT, CBT, and RF provided ratings of the 100 CPQ items to describe an ideal prototype session that adheres to the principles of their treatment model. Two Q-factor analyses with varimax rotation were conducted.Results: Expert clinicians reached a high level of agreement on their respective PDT and CBT prototypes. These prototypes loaded onto two independent factors. The RF process prototype loaded onto both factors.Conclusions: From the theoretical perspective of expert clinicians representing PDT and CBT, a focus on RF appears to be a common process factor in the way both treatment models are conceptualized. The CPQ can also be a useful instrument in teaching psychotherapy process from different theoretical perspectives and training future clinicians in their application. Future researchers can use these prototypes to explore process in actual sessions.